ANALISIS KEBIJAKAN EKONOMI PUBLIK TENTANG PELAYANAN KESEHATAN MASYARAKAT MISKIN DI RUMAH SAKIT MILIK PEMERINTAH (Implementasi Program Jamkesmas di Jawa Timur) - Anna Marina (BALANCE: Economic, Business, Management and Accounting Journal, 2008)
Various policies taken by the government to help poor people reduced to poverty burden. The policy of them are in the areas of health, which aims to facilitate / ease the poor to health. Since 1998 the government, in this case the Ministry of Health has launched a service improvement program for poor families, a program of JPS-BK (Social Security Network Health Sector) are sourced from the Asian Development Bank loan for basic services for poor families. This program lasted until 2002. The Government does not just stop in an effort to lighten the burden of the poor in the health sector, various policies have been taken, Beginning in 2008 Managed Care program, usually called HIP changed its name to Community Health Insurance (JAMKESMAS) with no change in the number of targets. This program aims to provide access to the public health service is very poor, poor and near poor who numbered 76.4 million inhabitants. Thus, the degree of public health is very poor, poor and near poor can be increased and indirectly can improve the quality and productivity of human resources in Indonesia. Health services for the poor provided by government hospitals in East Java province needs to consider the quality of services provided through the following aspects: cost of hospital services, hospital environmental safety, justice get service, clarity about roles and functions of officers who served, availability & understanding treatment and clarity of information on how to deliver information about the patient's illness. Keywords : JPKM,  Askeskin,  Jamkesmas,  Gakin, kualitas pelayanan.